Avaliação da intersetorialidade no programa saúde na escola: estudo de caso de um município de Minas Gerais - Luciana Terezinha da Silva (2023)
Intersectoriality is the articulation between subjects from different sectors, with different knowledge and constitutes a privileged strategy for facing complex social problems. In the field of Health, it can be understood as an articulated form of work with the purpose of producing more significant effects on the health of the population. The present study aimed to analyze the presence and development of intersectoriality among those involved in Health Promotion activities promoted by the School Health Program (SHP) in the municipality of Carandaí/ Minas Gerais (MG). A qualitative case study was carried out using in-depth interviews as a data collection instrument. To recruit the participants, three schools of the municipal school system and their respective Basic Health Units (BHU) were intentionally selected. In total, 30 participants of the SHP, including health professionals (n=10), education professionals (n=10) and parents or guardians of students (n=10) were invited to participate in this research and included upon acceptance through the Term of Free and Informed Consent (ICF). The interviews followed a guiding script, which had a triggering question ("Tell me what you know about the SHP in Carandaí") and some points to be explored, such as: 1) knowledge of the SHP and its purpose; 2) participation of the interviewee in SHP activities; 3) knowledge about those involved in the development of SHP activities; 4) knowledge about planning SHP activities in the municipality; 5) existence of coordination between the sectors involved; 6) knowledge about the results of the SHP in the municipality. For data analysis, the content analysis method was used, based on a logical/theoretical model and a matrix of indicators. The research revealed that the reach of intersectoriality goes through several challenges that need to be overcome. It is noteworthy that this advance can be facilitated by the regular training of the professionals involved in the SHP, by improvements in communication and in the strengthening of the bond between the sectors involved. In addition, it is important that there is equivalence between the health and education sectors in the political-managerial process and in the execution of activities. From this study was proposed the technical product – ebook- that aims to facilitate the planning and execution of oral health promotion actions developed in the SHP, deepen the knowledge about the Program and demonstrate, through workshops, ways to insert the theme of oral health in the school routine.